"(1)\\\\\n\\displaystyle\\textsf{Let the fraction be}\\hspace{0.1cm} \\frac{x}{y}\\\\\n\n\n\\frac{x}{y} = \\frac{3y}{y}\\\\\n \n\n\\displaystyle\\frac{3y - 1}{y + 2} = \\frac{5}{2}\\\\\n\n\n\\begin{aligned}\n2(3y - 1) &= 5(y + 2)\\\\\n6y - 2 &= 5y + 10\\\\\ny &=10 + 2 = 12\n\\end{aligned}\\\\\n\n\\therefore \\textsf{The original fraction is}\\hspace{0.1cm} \\frac{x}{y} = \\frac{36}{12}.\\\\\n\n\n(2)\\\\\n\n\n6\\hspace{0.1cm} \\textsf{chairs can be washed in} \\hspace{0.1cm}21\\hspace{0.1cm} \\textsf{minutes}. \\\\\n\n\n1\\hspace{0.1cm} \\textsf{chair can be washed in} \\hspace{0.1cm}\\frac{21}{6}\\hspace{0.1cm} \\textsf{minutes}. \\\\\n\n\\therefore 10\\hspace{0.1cm} \\textsf{chairs can be washed in} \\\\\\hspace{0.1cm}\\frac{21\\times 10}{6}= 35\\hspace{0.1cm} \\textsf{minutes}."
Comments
Leave a comment